An Analysis of Students’ English Learning Interest at Class IV of SDN 08 Cipondoh Tangerang City - Sintawati, Fairus; Asih Rosnaningsih (JEDLISH : Journal Of Education and English Language Teaching, 2021)
This study aims to determine students’ interest in learning English in fourth grade at SD Negeri 08 Cipondoh, Tangerang City. This study uses a qualitative approach with the type of qualitative descriptive research method. Qualitative research is used to identify students' interest in learning English. The subjects in this study were teachers and students of grade 4 SDN 08 Cipondoh Tangerang City. The type of research data consists of primary data and secondary data. The instruments in this study were observation guidelines, interviews, and questionnaires. In this study, the technique of checking the validity of the data used is the triangulation technique. The results showed that many students had a high interest in learning English.